Genetic and morphometric variation of Octopus vulgaris in the Benguela Current region - De Beer, Chénelle Lesley (Rhodes University, Faculty of Science, Department of Ichthyology and Fisheries Science, 2014)
The Benguela Current is a cold eastern boundary current located on the south-western coast of the African continent. The establishment of its present day features approximately two million years ago has triggered allopatric events which have driven genetic and/or phenotypic differentiation in many of the warm-temperate organisms that previously had continuous distributions along the south and west coast of southern Africa. However, since many of these species have responded differently, despite similar isolation times, research in this region provides a unique opportunity to increase our understanding of evolutionary processes. The common octopus (Octopus vulgaris, Cuvier 1797) is a coastal, sedentary species, inhabiting coral reefs or rocky environments at depths of up to a 100m. It is considered to be one of the most extensively studied cephalopod species due to its worldwide distribution. However, very little research has been conducted on O. vulgaris in southern Africa. In order to gain a holistic understanding of the effects of the Benguela Current on population connectivity, genetic and phenotypic diversity, and evolutionary history of O. vulgaris, a comparative genetic and morphological study was conducted across the Benguela region. A total of 168 specimens of O. vulgaris were collected from four different regions across the Benguela system. A small tissue sample was preserved in ethanol for molecular analysis, and the specimen was frozen whole for morphometric analysis in the laboratory. Octopus vulgaris genetic population structure and evolutionary history was investigated using a 580bp fragment of the mitochondrial cytochrome b (cytb) gene for 76 individuals located within the Benguela region, yielding 10 different haplotypes. AMOVA and pairwise FST analyses revealed significant genetic differentiation suggesting a northern-southern Benguela divergence. Estimates of time since most recent common ancestor, based on biogeographical calibrators and coalescent analyses, indicated that isolation between the Angolan and South African population occurred between ~231 Ka and 1 Ma. Mismatch distribution analyses revealed a past population expansion within the South African O. vulgaris roughly 129.31 Ka, whilst Bayesian skyline plots were indicative of gradual demographic growth within the Angolan population in the last ~100 Ka. Observed O. vulgaris population structure and demographic history was likely the result of historical climate-induced change within the system. Reconstruction of phylogenetic relationships within the Octopus genus, using cytb and COI suggest that O. vulgaris is not a monophyletic group and a major systematic revision is required. Furthermore, unidentified individuals from South Africa were found to group with species from Indo-West Pacific Oceans and were therefore considered to have been translocated through ballast water from Asia. While the molecular analysis indicated a significant northern-southern Benguela structure results from the principle component analysis (PCA) and discriminate function analysis (DFA) were unable to distinguish between O. vulgaris from different sampling localities throughout the Benguela Current region based on soft-parts, hard-parts and meristic characters. The lack of phenotypic variation, despite significant genetic divergence, highlights the importance of multi-method approaches in gaining a holistic understanding of the taxonomy and biogeography of species.
Keywords: Common octopus -- Africa, Southern; Common octopus -- Genetics; Common octopus -- Morphology; Common octopus -- Geographical distribution; Variation (Biology); Benguela Current